The role of gender in crop value chain in Ethiopia - Aregu, Lemlem; Puskur, Ranjitha; Bishop-Sambrook, C. (International Livestock Research Institute, 2011)
This paper has demonstrated that site-specific commodity-based gender analysis is essential for understanding the different roles of women and men in the production of specific commodities, marketing and decision-making, and their share in the benefits; identifying potential barriers for women’s and men’s participation in market-led development initiatives and technology adoption The gender analysis findings of the IPMS project across PLWs illustrate how this type of analysis potentially helps to explore challenges and to spot out the entry point for promoting gender equality and women’s empowerment through increasing women’s access to skills, knowledge, assets and increasing women’s participation in market-oriented agricultural production and their control over the benefits.